STUDI PEMILIHAN TANAMAN REVEGETASI UNTUK KEBERHASILAN REKLAMASI LAHAN BEKAS TAMBANG - Rr Diah Nugraheni Setyowati; Nahawanda Ahsanu Amala; Nila Nur Ursyiatur Aini (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2017)
The contribution of the mining sector to forest destruction in Indonesia reaches 10% and now drove to 2 million ha every year. To overcome this problem, it is necessary to reclaim the former mining area. One of the determinants of the success of reclamation is plant’s selection, in accordance with the condition of the land. In this case for revegetation activities need to pay attention between plant’s selectionspecies and plant growth requirements with the condition of the land, so that the reclamation success criteria can be achieved. This research uses descriptive analysis method, this method is done by describing the facts which followed byanalysis and provide sufficient understanding and explanation. Techniques of data collection using comparative analysis method by comparing various journals and other literature. Criteria for selection of tree species for ex-mining land can be seen from:(1) local species of pioneer, (2) fast growing but not in high cost, (3) produces litter that easy to decompose, (4) good root system and able to do reciprocal relationship with certain microba, (5) seed carrier, (6) easy and cheap in propagation, planting and maintenance. The success of revegetation depends on several things such as: preparation of planting, crop, plant maintenance and plant monitoring. Keywords: mining, reclamation, plant, revegetation